A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)
Code: La création musicale au Québec

Their Own Agenda: The History, Development, and Culture of Women's Orchestras Outside the United States - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Entrevista com a cantora e compositora Bïa Krieger [Entretien avec l'autrice-compositrice-interprète Bïa Krieger] - Cassiano, Raissa (Tradterm, 2018)
Radicada há mais de vinte anos na França e no Canadá, Bïa Krieger conquistou um público cativo nesses países, onde recebeu prêmios importantes, como o Grand Prix de l’Académie Charles Cros (França), Prix de l’Adisq (Canadá) e Félix du Meilleur Album Musiques du Monde (Canadá). Esta entrevista contempla o seu trabalho como versionista, com enfoque nas versões em francês para canções de Chico Buarque.

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)
Publisher: Circuit, musiques contemporaines

Broadcasting Queer Feminisms: Lesbian and Queer Women Programming in Transnational, Local, and Community Radio - Copeland, Stacey (Journal of Radio & Audio Media, 2018)
Notable radio scholars including Christine Ehrick, Phylis A. Johnson, and Caroline Mitchell have explored critical challenges of gender and sexuality radio research and its importance in relation to communities. A major issue faced in studying the early years of women’s history in broadcast is the ephemeral nature of the medium as many of the voices are lost in the ether, unrecorded or once deemed inessential to archive. Web-based radio and podcast archives provide renewed avenues for listening to lesbian and queer women’s radio across transnational borders yet many long running shows in Canada such as The Lesbian Show on Vancouver Co-Op Radio have only recently begun to surface as digital collections. As personal and institutional archives of lesbian and queer women radio begin to reach a public audience, analysis of radio works across decades of LGBTQ2+ activism and feminisms must be traced to understand the role of radio and digital radiogenic media in creating space and identity for queer activism. A turn to the past brings forward questions of analog and digital futures for radio and podcasting space as place to construct and shape queer and especially lesbian communities and identities in the North American broadcasting industry. Through research of notable live and pre-produced content including Dykes on Mykes on CKUT 90.3 FM, and The Lesbian Show on Vancouver Co-Op Radio, this work offers an exploration of radio and radiogenic media’s role in creating sonic space for queer and feminist subjectivities.
Publisher: Routledge _eprint: https://doi.org/10.1080/19376529.2018.1482899

Diane Dufresne. Aujourd'hui, hier et pour toujours - Dufresne, Diane (Éditions Libre Expression, 2018)
Diane Dufresne est l'une des plus célèbres voix de la chanson québécoise et figure parmi les artistes les plus importantes de notre époque. Sa virtuosité et sa créativité est reconnue tant au Québec qu'en Europe. À soixante-quatorze ans, elle poursuit activement sa carrière. Sa popularité est immense et, au fil des ans, elle a reçu de nombreuses distinctions. Cet ouvrage, élaboré en collaboration avec son époux, l'artiste sculpteur Richard Langevin, propose une rétrospective d'un parcours riche en événements et en succès. De Tiens-toé ben j'arrive! à Magie rose en passant par Les Violons du Roy, ce livre relate les grandes étapes de la vie professionnelle et personnelle de la chanteuse à partir de photos souvenirs et d'images inédites. Un véritable devoir de mémoire.

Pauline Julien, intime et politique - Ferland, Pascale (Office national du film du Canada, 2018)
Suivant un minutieux choix d'extraits d'entrevues, de spectacles et de photos, puisés à même un colossal et riche fonds d'archives, Pauline Julien, intime et politique nous entraîne dans le sillage de cette femme résolument libre et engagée, figure emblématique de la chanson et d'une époque charnière de l'histoire du Québec.

On feeling mighty real: devenir gay à Montréal pendant l’ère disco dans Funkytown, de Daniel Roby - Foerster, Maxime (Contemporary French Civilization, 2018)
Our catalogue of journals

Représentation de soi et matérialité des lettres dans la correspondance amoureuse entre Pauline Julien et Gérald Godin (1962-1993) - Germain, Emmanuelle (Université Laval, 2018)
Pauline Julien et Gérald Godin ont entretenu une correspondance amoureuse s’étendant sur plus de trente ans, soit de 1962 à 1993. Quelques-unes de leurs lettres ont fait l’objet d’une publication, La Renarde et le mal peigné (Leméac Éditeur, 2009), grâce à Pascale Galipeau, fille du comédien Jacques Galipeau et de Pauline Julien. Mais c’est avant tout le corpus inédit de plus de 400 lettres non reprises, découvertes dans les fonds d’archives à BAnQ, qui feront l’objet de nos recherches. Outre sa « fonction documentaire » (Jaubert, 2010a : 74), cette correspondance permet de voir la mise en scène par laquelle s’élabore la construction du moi de Julien et de Godin. Au fil de leur échange épistolaire, chacun joue sur l’impression qu’il tente de produire sur l’autre, de manipuler la mise en scène du moi qui régule leur interaction amoureuse. Dans l’ensemble des lettres, cette présentation de soi relève d’une complexion plus vaste que celle qui se dégage des choix éditoriaux effectués dans La Renarde et le mal peigné, restreinte à la relation amoureuse. Permettant d’éclairer la relation personnelle entre Julien et Godin, ainsi que leurs trajectoires artistiques respectives, cette correspondance constitue le lieu d’une négociation entre leurs postures publiques (poète journaliste puis ministre et chanteuse engagée) et intimes (homme de lettres au foyer et femme de profession). De fait, même si leurs échanges restent intimes, il y a là une présentation de soi qui se confronte à la nécessité de négocier avec la médiatisation de leur figure publique, celle-ci influençant leur part de contrôle sur la figure intime qu’ils tentent de dessiner dans leur correspondance. Des textes de Ruth Amossy (La présentation de soi. Ethos et identité verbale et Images de soi dans le discours : la construction de l’ethos), d’Anna Jaubert (« L’éthos de l’épistolier au miroir de l’autre ») et d’Arlette Farge (Le goût de l’archive), constitueront les bases théoriques de notre étude.
Accepted: 2018-12-07T00:01:21Z

La renarde et le mal peigné - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2018)
Dans ces « fragments de correspondance amoureuse », on découvre Pauline Julien et Gérald Godin comme jamais on ne les avait vus, comme jamais plus on ne les verra. Lui, jeune loup puis loup mature, passionné, dévoué à la cause et amoureux. Elle, mère, chanteuse, absente souvent, incertaine et amoureuse. Elle que le doute assaille, toujours. Lui, de plus en plus sûr. C’est un magnifique tango qui se déroule sous nos yeux, on s’attire et se repousse dans le même paragraphe. Et c’est beau. Que c’est beau! La poésie qui les habite en permanence est suffisante pour rendre n’importe quel esprit jaloux, suffisante pour affadir n’importe quel amour. Pascale Galipeau, fille de Pauline Julien, a dû braver objections et réprimandes pour publier ces lettres. On ne peut que la remercier à genoux et lui baiser les mains de ne pas avoir cédé.

Les épreuves du travail musical : la persévérance des musiciens et musiciennes au Québec - Lavoie-Ricard, Olivier (Université de Montréal, 2018)

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

Avant-propos. Pour des musicien·ne·s organiques ? - McKinley, Maxime (Circuit, 2018)
Publisher: Circuit, musiques contemporaines
Keywords: Inclure l'avant-propos ?

L’intermédialité autochtone dans l’œuvre de Natasha Kanapé Fontaine : mémoire, oralité et territoire - Morin-Martel, Florence (Université de Montréal, 2018)
Ce mémoire explore la notion d’intermédialité autochtone au sein de l’oeuvre de Natasha Kanapé Fontaine. Les imbrications entre les médias seront notre point d’appui pour penser les questions de l’esthétique dans l’art autochtone actuel. Par le biais de la représentation d’un média dans un autre, nous aborderons ainsi la réactualisation des traditions orales telles que le conte, le mythe, le chant et le tambour au sein des productions de cette artiste. Notre parcours observera les structures intermédiales qui mettent en exergue la mémoire ainsi que les connaissances ancestrales. Les croisements entre l’identité et le territoire seront également discutés dans l’optique des représentations intermédiales. Ainsi, les phénomènes d’affirmation et de réactualisation des savoirs se déploient par l’utilisation de divers médias. De ce fait, la résistance environnementale et culturelle ainsi que la néo-oralité sous-tendent l’oeuvre de l’artiste et s’expriment à travers les territoires imaginaires et médiatiques.

Isabelle Panneton. De la rigueur à la liberté de création - Nattiez, Jean-Jacques (La création musicale au Québec, 2018)
Code: La création musicale au Québec

"The Canadian Inhabitants are Remarkably Fond of Dancing": Reading the African Musicians in George Heriot's Minuet of the Canadians (1807) - Nelson, Charmaine A. (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues–a group of established and up-and-coming artists, scholars, and cultural critics–argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History–an African Canadian Art History

Le hip-hop avec des gants blancs - Néméh-Nombré, Philippe (Liberté, 2018)
Réflexion sur la dépolitisation et l’éclaircissement du hip-hop lors de son passage dans la culture de masse.

Du teweikan à l'électro : voyage aux sources de la musique autochtone - O'Bomsawin, Kim (Société Radio-Canada, 2018)
Il y a très longtemps, hommes, femmes et enfants de tous âges, clans, allégeances et nations se sont unis au son des vibrations du teweikan, qui signifie tambour traditionnel. Entre les mains des auteurs-compositeurs-interprètes Pakesso Mukash (Cri/Abénaquis), Shauit (Innu) et Moe Clark (Métis), il s’avère toujours un puissant outil de communion. Sous des airs désormais folk, électros ou reggae, le teweikan s’efforce encore aujourd’hui de créer des ponts entre les générations, les vivants et les morts, les territoires, ainsi que les conquis et les insoumis. Nous en profiterons pour remonter le fil de l’histoire de la musique des Premières Nations, du teweikan à l’électro, de Montréal à la baie d’Hudson, des plaines canadiennes à la Côte-Nord.

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

Guerre ou pas, j'irai danser la veille du jour de l'an. Chroniques d'une danseuse invétérée - Roquigny, Peggy; Saint-Jacques, Denis; Des Rivières, Marie-Josée (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)

Alys vue par Rita - Savoie, Chantal (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Durant la Crise et la Deuxième Guerre mondiale, on imagine Montréal sans ressources pour la culture, Montréal ligotée, bâillonnée. C’est bien mal la connaître. Au contraire, elle s’engage alors dans une des grandes révolutions du siècle, soit celle des médias qui parlent et qui chantent. Le cinéma, la radio, le disque y recomposent l’environnement du divertissement et des arts d’une manière surprenante. Et ces nouveaux médias ne remplacent pas la presse, le concert ou le théâtre, ils s’y ajoutent, multipliant l’offre à un point qu’on n’avait encore jamais vu. Cela révolutionne la vie chez soi où, en plus du journal et du magazine, dont les tirages explosent, le piano rencontre deux nouveaux concurrents, le gramophone et le récepteur radio. Sans être riche, on peut entendre des concerts, même de musique autochtone et de grandes vedettes, chez soi, on peut « swinger » sur le jazz chez soi. On peut aussi sortir, ce que facilite un urbanisme stimulé par les nouvelles gares. Les salles de cinéma, de danse, se multiplient. C’est là qu’on se laisse emporter par le jazz ou « Tico, tico ». On se plaint chaque année que le théâtre se meurt ? Ça n’empêche pas une rencontre entre Shakespeare et Alfred Pellan. Ou d’aller entendre un transethnique prêcher l’écologie. Et aussi de s’habiller à la mode pour aller skier sur la montagne. Ce bouleversement transforme le visage de la ville, comme nous le révèlent les peintres juifs, les radioromans, ou deux œuvres majeures du temps, Two solitudes et Bonheur d’occasion. On ne verra plus jamais Montréal avec les mêmes yeux, on n’entendra plus jamais Montréal avec les mêmes oreilles. Avec des textes de Marie Beaulieu, Justin Bur, Marc H. Choko, Marie-José des Rivières, Dominic Hardy, Lorne Huston, Germain Lacasse, Laurier Lacroix, Marie-Thérèse Lefebvre, Renée Legris, Jocelyne Mathieu, Sandria P. Bouliane, Adrien Rannaud, Peggy Roquigny, Lucie Robert, Mario Robert, Denis Saint-Jacques, Chantal Savoie, Esther Trépanier et Elspeth Tulloch.

Music from the Wrong Place: On the Italianicity of Quebec Disco - Straw, Will (Criticism, 2018)
One of my favorite compilation CDs of the last few years is Unclassics: Obscure Electronic Funk and Disco, 1975–1985, released in 2004 on the Environ label. The thirteen tracks on Unclassics were collected and remixed by house/techno artist Morgan Geist, who offers them as all-but-forgotten dance music gems from just outside an Anglo-American musical axis, from places like Spain and Italy. The style that ostensibly unites these tracks is “Eurodisco,” though, as we shall see, that label does not accurately subsume all of them. “Italo-disco” seems an even cruder reduction, but circulates among critics, fans, and collectors as a meaningful label for much of the music gathered here. While some of the cuts on Unclassics have long been the idiosyncratic favorites of DJs or dance music collectors, more is going on here than the resurrection of cultish or neglected treasures. Unclassics is one milestone within the significant rehabilitation of European and Italian disco that has unfolded over the last decade. Mixed Up in the Hague, Vol. 1, a compilation first released privately in 1999, was a key event in this rehabilitation; other collections, like I-Robots: Italo Electro Disco Underground Classics and Confuzed Disco: A Retrospective of Italian Records, have followed. Zyx, the Germany-based label that dominated the field in the 1980s and early 1990s, is actively marketing dozens of compilations of its own Italo-disco from that period. The garish red and green covers of Zyx’s Italo anthologies, which filled the discount cassette bins of European airport stores fifteen years ago, have been redesigned so that they now look authoritative and curatorial. Radio and DJ sets devoted to this music now abound on the Internet. Think Italy. Without claiming mind-reading powers, it’s a comfortable prediction you’ve already got tacky piano sample records and frenzied all-night clubbing in mind, a nation that when it isn’t knocking out club records by the cartload likes nothing more than to party all night on a hillside by the sea. Italian music has been in and out of style more often than the flares revival. There are enough piew-piew-piew zaps during these 55 minutes to wipe out a small nation of roller skaters. For almost two decades, tracks like those collected on Unclassics held the status of morbid symptoms, reminders of the decay and dispersion of dance music in the years between disco and house music. Even as they reclaim these tracks as lost gems, the liner notes to Unclassics embrace that morbidity, relishing the ways in which so many of these pieces are seen to have gotten things wrong. My favorite track on Unclassics is a Spanish cut from 1979, “Margherita,” whose guiltless dishing out of pleasures betrays the compilation’s broader sensibility. Piercing little synth notes alternate with thick, rolling movements that could drive an army forward. Mariachi horns interweave with tinny keyboard glissandos in rounding out sections. Changes come precisely when we want them; each gimmicky sound or flourish dutifully returns just as we start to miss it. As “Margherita” moves in unstoppable fashion around its wheel of styles and sections, it is easy to think that this is music trying too desperately to be liked. Dominant understandings of the European contribution to disco read its influence selectively, focusing on the robotic, synthesized sounds of Kraftwerk or Giorgio Moroder. These versions of Eurodisco’s history link such figures as Can, Patrick Cowley, Afrika Bambaataa, and Juan Atkins in a heroic story that sends disco to Europe so that it may return, reinvented, to an American underground able to realize its radical potential. When Eurodisco is remembered for its sleek mechanical control, however, what gets forgotten is the lush extravagance that seemed to mark so much of it. As early as 1977, North American critics had recourse to a well-entrenched moral geography in characterizing disco music from continental Europe as “florid,” given to flamboyant passion and bombastic overlays of effects.1 Arguably, the peculiarity of so much Eurodisco came from the ways in which its extravagant lushness often went hand in hand...

“Come One, Come All”: Blackface Minstrelsy as a Canadian Tradition and Early Form of Popular Culture - Thompson, Cheryl (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues–a group of established and up-and-coming artists, scholars, and cultural critics–argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History–an African Canadian Art History